Facets of a transforming China resource, trade and equity - Yeoh, Emile Kok-Kheng (Institute of China Studies, Universiti Malaya, 2008)
This book is a collection of research papers on various important facets of a China in transformation. Despite the highly remarkable economic achievement in recent decades, China's phenomenal rise has also brought to world attention a host of perplexing questions related to her increasing economic strength, implications of her "footprint" around the world in her relentless quest for energy resources to drive her continued growth, and last but not least, her expanding interregional and urban-rural disparities on the domestic front.